Control systems for DC motor as port-controlled hamiltonian system - (:unkn) unknown (Lviv Polytechnic Publishing House, 2016)
One of the newest methods of control system design for DC motor as a part of electromechanical systems are energy-based approaches. The regulation in such systems is realized by forming energy function of the system. This article contains comparative analysis of simulation results of existing control systems, their applications and basic principles explanation. It was shown that using mechanical damping provides highly effective control and there are still many possibilities to increase energy-shaping system’s efficiency.
Keywords: DC motor; energy-based approach; control system; energy-shaping control system; structural and parametric synthesis; comparison; systems of modal regulation; cascade control systems